ChemInform Abstract: ICI‐Mediated Intramolecular Twofold Iodoarylation of Diynes and Diynyl Diethers and Amines: Synthesis of Bis(2H‐hydronaphthalene and chromene) and 2H‐Quinoline Bearing an Alkenyl Iodide Moiety. Issue 17 (28th April 2014) - Mo, Juntae; Choi, Wonseok; Min, Jiae; Kim, Cheol‐Eui; Eom, Dahan; Kim, Sung Hong; Lee, Phil Ho
Abstract The reaction can be applied to a broad range of diynes under mild conditions with good to high yields.